Developing government bond markets : a handbook - International Monetary Fund.; World Bank. (Washington, D.C. : World Bank : International Monetary Fund, 2001)
The handbook was prepared by the staff of the World Bank and the International Monetary Fund. It is likely to be seen as a "benchmark" on the issue, discussing several important aspects of debt markets in a very pragmatic and useful manner. Although there is no single recipe for success, this handbook will surely help government officials around the world, particularly debt managers, to deal with one of the most complex and significant areas in economic policy and public finance.
Includes bibliographical references.
rpm 02/07/13, usc 14/06/17
Loans
Keywords: Bond market; Government securities